Implementation Of Special Protection For Children As Victims Of Sexual Violence In The D.I. Yogyakarta Region - Sri Rejeki Mutmainah, Mita; Manik, Jeanne Darc Noviayanti; Agustian, Rio Armanda (PT. Anagata Sembagi Education, 2024)
The younger generation under the age of 18, including those who are still in the womb, is categorized as children. They are the successors of the nation's ideals and the foundation of hope for the nation's progress in the future, so they need to get protection and guidance in order to contribute optimally to national development. Children, in accordance with Law No. 35 of 2014 Article 1 number 2, are entitled to protection. This protection aims to ensure that they can live, grow, develop, and contribute optimally in accordance with human dignity, as well as avoid violence and discrimination. Behind these rights, children have limitations in protecting themselves from various dangers that can interfere with their mental, physical, and social health, as well as their lives as a whole. Therefore, they need help and support from others to ensure their safety and well-being. The state, both through the central and local governments, as well as related institutions, is required to provide Special Protection to children. This protection is provided in certain situations and conditions to ensure a sense of security for children from various threats that can endanger their growth and development. Ironically, despite various regulations and protection efforts, the rights of many children are still violated. They are victims of various forms of violence, exploitation, mistreatment, discrimination, and even inhuman actions. One of the rampant occurrences is sexual violence against children. Worse, the impact of sexual violence on children does not only depend on the type, but also how often they experience it. The more often, the greater the trauma suffered and the longer the recovery..